2008
DOI: 10.1111/j.1440-1746.2007.04911.x
|View full text |Cite
|
Sign up to set email alerts
|

Baseline cholesterol is associated with the response to antiviral therapy in chronic hepatitis C

Abstract: Baseline serum total cholesterol levels and BMI could be helpful in discriminating responders to antiviral therapy among patients with HCV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
47
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 34 publications
4
47
1
Order By: Relevance
“…Despite an association of smoking with SVR and clear effects on serum lipids, we found no significant correlation of lipid parameters with SVR. This is in contrast to the data reported by Economou et al, who found higher serum baseline levels of total cholesterol and LDL cholesterol to be associated with better response towards PEG-IFN, suggesting that smoking might have a positive effect for the treatment response as smoking leads to higher baseline total and LDL cholesterol concentrations [5][6][7][8]28]. Since it is known that statin treatment might improve SVR rates, patients with this medication were excluded from the analysis [10][11][12].…”
Section: Matched Pair Analysis (Mpa)contrasting
confidence: 79%
See 1 more Smart Citation
“…Despite an association of smoking with SVR and clear effects on serum lipids, we found no significant correlation of lipid parameters with SVR. This is in contrast to the data reported by Economou et al, who found higher serum baseline levels of total cholesterol and LDL cholesterol to be associated with better response towards PEG-IFN, suggesting that smoking might have a positive effect for the treatment response as smoking leads to higher baseline total and LDL cholesterol concentrations [5][6][7][8]28]. Since it is known that statin treatment might improve SVR rates, patients with this medication were excluded from the analysis [10][11][12].…”
Section: Matched Pair Analysis (Mpa)contrasting
confidence: 79%
“…Hepatitis C virus partially interacts with LDL receptors when entering the cell, suggesting a role for lipids in regulating HCV clearance [8]. Higher serum baseline levels of total cholesterol and LDL cholesterol were reported to be associated with better response towards PEG-IFN [8].…”
Section: Do the Effects Of Smoking On Lipid Metabolism Affect Svr Rates?mentioning
confidence: 99%
“…Indeed, HCV circulates in patient sera in the form of triglyceride-rich particles and consequently, lipoproteins and lipoprotein receptors may play an important role in hepatic virus uptake. 4,5 For reasons of the association of HCV with apoB-and apoE-containing low-density and very low density lipoproteins, the LDL receptor has been proposed as a potential entry factor for HCV. Although the function of LDL-R in…”
Section: Acknowledgementmentioning
confidence: 99%
“…[2][3][4][5][6] The direct relationship between HCV entry into cells is a multi-step and slow process. It is believed that the initial capture of HCV particles by glycosaminoglycans and ⁄ or lipoprotein receptors is followed by coordinated interactions with the scavenger receptor class B type I (SR-BI), a major receptor of high-density lipoprotein (HDL), the CD81 tetraspanin, and the tight junction protein Claudin-1, ultimately leading to uptake and cellular penetration of HCV via low-pH endosomes.…”
mentioning
confidence: 99%
“…2 Recent evidence from small retrospective studies suggests that elevated low-density lipoprotein (LDL) levels may be associated with higher SVR rates in patients infected with HCV genotype 1. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] In vitro data suggest that lipid-lowering agents (3-hydroxy-3-methylglutaryl coenzyme A reductase inhibitors or statins) may inhibit viral replication. However, cell culture models of HCV infection have demonstrated that anti-HCV activity is not the same for all statins: fluvastatin, atorvastatin, simvastatin, and lovastatin inhibit viral replication to variable extents, whereas pravastatin and rosuvastatin have little to no anti-HCV activity.…”
mentioning
confidence: 99%